Modernisasi Pendidikan Islam di Dunia - Nurhasan Nurhasan (STAI Al-Mas'udiyah, 2024)
This research aims to find out the background of Islamic education modernization, find out the urgency of Islamic education modernization, and find out the pattern of Islamic education modernization in the world. The method used in the preparation of this research is a qualitative method which in the data collection technique uses literature studies. The results of the analysis show that the background that is developing today in the modernization of Islamic education is the existence of internal and external factors. The internal factors are: 1) Muslims need a truly reliable Islamic education system in order to produce quality Muslim people, 2) the religion of Islam through the holy verses of the Qur'an tells and encourages Muslims to always think, and metaphorize; reading and analyzing everything to then be applied or even able to create new things from what has already existed. Meanwhile, the external factor that causes the importance of modernizing Islamic education is to catch up with Muslims against other nations, as well as to answer the challenges of changing times that are so dynamic. Meanwhile, the urgency of modernizing Islamic education is very important to invite third world nations that are still at the level of backwardness and backwardness to accept western standards that they consider to be ideal. And there are three patterns of modernization of Islamic education, namely: 1) Groups that are oriented towards the modern education pattern in the West. 2) Islamic Education Modernization Movement (Renewal) oriented to pure Islamic sources. 3) Educational reform efforts oriented to nationalism.